A preparation method of butanediol polyester

The catalyst ease is solved by using the combination of catalyst A composed of titanium compounds, chelating ligands and organic bases in the synthesis of butanediol polyester, and catalyst B composed of titanium compounds, 1,4-butanediol and phosphate esters. The problem of hydrolysis and excessive THF by-products achieves high intrinsic viscosity, light color and low carboxylic content of the polyester.

CN116574247BActive Publication Date: 2025-02-11ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310793932.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-11
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

In the synthesis of butanediol polyester, the catalyst is prone to hydrolysis, the yield of by-product THF is too high, the product discoloration during the polycondensation stage, and the low viscosity of the characteristic, resulting in poor product quality.

Method used

Using a combination of catalyst A and catalyst B, catalyst A consists of titanium compounds, chelating ligands and organic bases during the esterification process, and catalyst B consists of titanium compounds, 1,4-butanediol and phosphate during the polycondensation process. Composition, through the coordination structure and composition of these catalysts, the hydrolytic stability and reaction activity of the catalyst are improved.

Benefits of technology

It significantly improves the hydrolysis stability and reaction activity of the catalyst, reduces the generation of THF by-products, and improves the color and inherent viscosity of the polyester. The obtained butylene glycol polyester has high intrinsic viscosity, light color, low carboxylic content and Few by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116574247B_ABST
    Figure CN116574247B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer synthesis, and discloses a method for preparing butanediol polyester. The method comprises the following steps: using diol and dibasic acid or diester thereof as raw materials, preparing butanediol polyester through esterification and polycondensation; adding catalyst A to carry out catalytic esterification during the esterification process, and adding catalyst B to carry out catalytic polycondensation during the polycondensation process; the diol comprises 80-100 mol % of 1,4-butanediol and 0-20 mol % of other diols; the catalyst A comprises a titanium compound, a chelated ligand and an organic base; the catalyst B comprises a titanium compound, 1,4-butanediol and a phosphate, the catalyst has high hydrolysis stability, and the prepared butanediol polyester has multiple excellent properties such as high intrinsic viscosity, light color and low terminal carboxyl content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer synthesis, and in particular to a method for preparing butanediol polyester. Background Art

[0002] Polybutylene terephthalate (PBT) is a thermoplastic plastic. Due to its excellent heat resistance, chemical corrosion resistance, insulation performance, etc., it is widely used in automobile manufacturing, electronic and electrical manufacturing, optical fiber sleeves, office machinery and other fields. The aliphatic-aromatic copolyesters prepared by co-condensation of aromatic dibasic acids or their diesters, fatty acid dibasic acids or their diesters and aliphatic diols have the characteristics of biodegradability of aliphatic polyesters and high melting point, fast crystallization rate and excellent mechanical properties of aromatic polyesters. It is an important and widely used biodegradable polymer material. Among them, the most important are poly(terephthalic acid-co-adipate) (PBAT) and poly(terephthalic acid-co-succinate) (PBST) with 1,4-butanediol (BDO) as the diol component.

[0003] For convenience, polyesters and copolyesters with 1,4-butanediol as the diol monomer or the main diol monomer are collectively referred to as butanediol polyesters. The synthesis process is usually divided into two stages: esterification (or transesterification) reaction and polycondensation reaction. During the synthesis process, not only do the main reactions such as esterification and polycondensation occur to increase the molecular weight of the polymer, but due to the high reaction temperature, various side reactions also occur, resulting in an increase in the yield of the by-product tetrahydrofuran (THF), a darker color of the polyester, and an increase in the content of terminal carboxyl groups, thereby affecting the product quality. The presence of terminal carboxyl groups has an adverse effect on the processing stability, storage stability and durability of polyesters.

[0004] Catalysts are the key to promoting the molecular weight growth of polyester and inhibiting side reactions. At present, highly active titanium catalysts such as tetrabutyl titanate (TBT) and tetraisopropyl titanate (TPT) have been successfully used in the industrial production of PBT and its copolyesters. Since polyester raw materials often contain a certain amount of moisture, especially diols are easy to absorb water, and the reaction process, especially the esterification process, will also produce water, so the esterification reaction system contains a certain amount of moisture. Compared with other catalysts, titanates are prone to hydrolysis during the polyester synthesis process, especially the esterification process, which not only leads to catalyst deactivation, but also the generated titanium dioxide and titanium polymers remain in the PBT resin, resulting in quality problems such as deterioration of its fog value and increase of impurities, or are deposited on the inner surface of the equipment, gradually causing problems such as poor heat transfer effect and pipeline blockage.

[0005] Another problem with the use of titanium catalysts to synthesize polyesters is the discoloration of the polymer. Titanate catalysts often cause serious discoloration when used for ethylene glycol polyesters. Although the discoloration is not as significant as that of ethylene glycol polyesters when used for the synthesis of butanediol polyesters, there is still a significant discoloration, especially for PBAT. The color of butanediol polyester can be improved by adding stabilizers or using modified titanium catalysts (such as CN113388100A), but there is still the problem of dark color or light but unstable color (the color becomes darker during storage and processing).

[0006] Therefore, how to produce high-quality products with high intrinsic viscosity, light color, and low terminal carboxyl content while inhibiting catalyst hydrolysis and the formation of tetrahydrofuran by-products is a key issue that needs to be solved in the synthesis of butanediol polyester.

[0007] Titanium glycolate is a solid catalyst. Ethylene glycol and titanium form a five-membered ring chelate structure. The thermodynamic stability of the ring is high, so it has good hydrolysis resistance and can show good catalytic effect in the polycondensation process. However, its water resistance is only improved to a certain extent compared with alkoxy titanium at room temperature, but there is no report on its hydrolysis stability at high temperature, that is, the actual esterification or polycondensation reaction temperature. In fact, these titanium alcohol catalysts produce white hydrolysis precipitates within 30 minutes of heating and reflux (about 210°C) in aqueous BDO solution, indicating that the hydrolysis stability is still poor in the application environment of the catalyst, that is, at the esterification temperature of 180-230°C, and a series of problems such as catalyst activity reduction, polyester quality deterioration, and equipment fouling caused by catalyst hydrolysis will still occur.

[0008] For the color problem of polyester finished products, phosphate is often added to improve the color in the prior art. For example, patent CN105131269A discloses a method for preparing a titanium-phosphorus coordination composite catalyst with phosphate as a catalyst component and a PBS production method using the catalyst. This catalyst is used in PBS production. The melt index of the produced PBS is lower than 3g / 10min (190°C, 2.16kg), the intrinsic viscosity reaches 2.05dL / g, the number average molecular weight is more than 100,000, and the L value is ≥80, the a value is ≥-0.43, and the b value is ≤5.24. The color value is much better than the national standard requirements. However, the reaction time is still about 6 hours, and the relevant esterification effect is not reported. It can be seen that adding a phosphate component as a stabilizer in the catalyst has a significant effect on improving the color of the polyester product, but it will lead to a decrease in the catalytic activity of the catalyst, which will bring about a decrease in the esterification rate, an increase in THF byproducts, and a decrease in the molecular weight of the polyester product.

[0009] In summary, there is still a lack of synthesis technology that can effectively avoid high-temperature hydrolysis of catalysts and inhibit the formation of THF while synthesizing high-quality butanediol polyesters with high intrinsic viscosity (>1.0dL / g), light color (b value <10), and low carboxyl content (less than 15mol / t, or even less than 10mol / t). Summary of the invention

[0010] The invention aims at the problems that the catalyst in the esterification stage of butanediol polyester synthesis is easy to hydrolyze, the yield of the byproduct THF is too high, the product in the polycondensation stage is discolored, the intrinsic viscosity is low, etc., and provides a method for synthesizing butanediol polyester. The method can not only greatly improve the hydrolysis stability of the catalyst in the polymerization, but also maintain the high reaction activity, excellent fluidity and dispersibility of the catalyst, so as to obtain butanediol polyester with high intrinsic viscosity, light color, low carboxyl content and less by-products.

[0011] The butanediol polyester described in the present invention refers to a polyester and / or copolyester synthesized using 1,4-butanediol as the sole or main diol monomer.

[0012] A method for preparing butanediol polyester comprises the following steps: using diol and dibasic acid or its diester as raw materials, preparing butanediol polyester through esterification and polycondensation; adding catalyst A to catalyze esterification during the esterification process, and adding catalyst B to catalyze polycondensation during the polycondensation process;

[0013] The diol comprises 80-100 mol % of 1,4-butanediol and 0-20 mol % of other diols;

[0014] The catalyst A comprises a titanium compound, a chelated ligand and an organic base;

[0015] The catalyst B includes a titanium compound, 1,4-butanediol and a phosphoric acid ester.

[0016] The present invention uses catalyst A to catalyze the esterification process, wherein the chelated ligand and the organic base jointly coordinate the titanium atom, which greatly improves the hydrolysis stability of catalyst A, especially the hydrolysis stability under high temperature conditions, so that it can still maintain good hydrolysis stability at high temperature (esterification or transesterification reaction temperature), has high catalytic activity, can reduce the generation of titanium dioxide or titanium polymer precipitation in the polyester production process, and maintain a very low THF yield (less than 8%). At the same time, in the polycondensation stage, a phosphate ester and titanium coordinated alcohol titanium phosphorus catalyst B is added, which is in a liquid state, that is, the problem that some phosphate esters have a low boiling point and are easy to volatilize, and solid phosphate esters are not easy to add is solved, and the hydrolysis stability of the catalyst is improved to a certain extent. While maintaining high catalytic activity, catalyst B significantly improves the color of the polyester product (b* value <10). Catalyst A and catalyst B are used in combination to obtain butanediol polyester with an intrinsic viscosity of more than 1.0 dL / g, a light color b* value of less than 10, and a carboxyl content of less than 15 mol / t or even less than 10 mol / t.

[0017] Catalyst A has excellent hydrolysis stability, high catalytic activity in both the esterification stage and the polycondensation stage, and good selectivity in the esterification stage. The THF yield is low, but the obtained polyester generally has poor color, which affects the further application of polyester products. Catalyst B contains more phosphorus compound components, which have a greater impact on the activity of the titanium alcohol catalyst. When used in the esterification reaction, not only is the catalytic activity and selectivity slightly poor, but the THF yield is also high. The two are used together, with catalyst A used in the esterification stage and catalyst B used in the polycondensation stage, to obtain polyester products with very excellent comprehensive performance. .

[0018] The molar ratio of the chelate ligand to the titanium compound in the catalyst A is (2-100):1, such as 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100, 65:100, 70:100, 75:100, 80:100, 85:100, 90:100, 95:100, or any value therebetween. Preferably, it is (2-50):1; within this preferred composition range, an excess of the chelate ligand can completely react the titanate raw material, and the catalyst A maintains good fluidity while having a high titanium content.

[0019] The molar ratio of the organic base to the titanium compound in the catalyst A is (0.5-8):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, or any value therebetween. Preferably, it is (1-4):1. Within this preferred composition range, the synthesized catalyst has both good fluidity and hydrolysis stability.

[0020] The molar ratio of 1,4-butanediol to the titanium compound in the catalyst B is (8-50):1.

[0021] The molar ratio of the phosphate ester to the titanium compound in the catalyst B is (0.1-2): 1, preferably (0.5-1.5): 1. Within this preferred composition range, the use of this catalyst system can obtain polyester having both high intrinsic viscosity and good color.

[0022] The chelating ligand is a diol or a beta-dicarbonyl compound containing an ortho-hydroxyl group.

[0023] When the chelating ligand is a diol containing an ortho-hydroxyl group, the preparation process of the catalyst A comprises: reacting raw materials including a titanium compound, a chelating ligand and an organic base at 160-180° C. for 0.5-4 hours to obtain the catalyst;

[0024] Preferably, the titanium compound, the chelate ligand and the organic base can be added simultaneously to react together, or two raw materials can be reacted first and then the other raw material is added to react.

[0025] For example, in plan I:

[0026] 1) mixing the chelating ligand and the organic base in a molar ratio of 160-180° C. for 0.5-4 h;

[0027] 2) adding the titanium compound to the reaction mixture obtained in 1), and reacting with continuous stirring at 160-180° C. for 0.5-4 h to obtain catalyst A.

[0028] Or, Option II:

[0029] 1) reacting an organic base with a titanium compound at 160-180° C. for 0.5-4 h;

[0030] 2) adding the chelating ligand to the reaction mixture obtained in 1), and continuously stirring the reaction at 160-180° C. under nitrogen protection for 0.5-4 h to obtain catalyst A.

[0031] Or, Option III:

[0032] 1) mixing the chelate ligand with the titanium compound, reacting at 160-180° C. for 0.5-4 h, or at 60-160° C., 10 kPa-0.2 kPa for 0.5-4 h;

[0033] 2) adding an organic base to the reaction mixture obtained in 1), and continuously stirring the reaction at 160-180° C. under nitrogen protection for 0.5-4 h to obtain catalyst A.

[0034] When the chelating ligand is a β-dicarbonyl compound, the preparation process of the catalyst A comprises: reacting the titanium compound and the chelating ligand at 60-120° C. for 15-30 minutes under vacuum; then adding an organic base and continuing the reaction at normal pressure for 15-30 minutes to obtain the catalyst A.

[0035] When the chelating ligand is a diol containing an ortho-hydroxyl group, the molar ratio of the chelating ligand to the titanium compound is (20-100):1;

[0036] When the chelating ligand is a β-dicarbonyl compound, the molar ratio of the chelating ligand to the titanium compound is (2-8):1;

[0037] The structure of the diol containing ortho-hydroxyl group is shown below:

[0038]

[0039] Wherein, R1 and R2 are independently selected from H, CH3, CH2CH3, CH2CH2CH3 or CH2CH2CH2CH3;

[0040] The β-dicarbonyl compound includes one or more of acetylacetone, ethyl acetoacetate, dimethyl malonate, and diethyl malonate.

[0041] Preferably, the chelating ligand includes one or more of ethylene glycol, 1,2-propylene glycol, 1,2-butylene glycol, 1,2-pentanediol, 1,2-hexanediol, 2,3-butylene glycol, acetylacetone, and ethyl acetoacetate. Ethylene glycol and acetylacetone are common chelating ligands that are easier to obtain and have lower costs.

[0042] The preparation method of the catalyst B comprises the steps of:

[0043] The raw materials including titanium compound, 1,4-butanediol and phosphate are reacted at 160-180° C. under nitrogen protection for 0.5-4 hours or at 60-120° C. under vacuum conditions for 0.2-1 hour to obtain the catalyst B.

[0044] The organic base includes alcohol amine compounds, pyridine, amidine or guanidine;

[0045] The titanium compound is a compound having the general formula Ti(OR)4, wherein R is a straight chain or branched alkyl group selected from 1 to 10 carbon atoms;

[0046] The phosphate ester includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, triisopropyl phosphate, tributyl phosphate, dibutyl phosphate, triphenyl phosphate, and triethyl phosphoacetate;

[0047] The other diols include any one or more of ethylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, and cyclohexane-1,4-dimethanol;

[0048] The dibasic acid or diester thereof includes any one or more of an aliphatic dibasic acid or diester thereof, an alicyclic dibasic acid or diester thereof, and an aromatic dibasic acid or diester thereof.

[0049] Preferably, the organic base includes one or more of ethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, triisopropanolamine, diglycolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), hexacyclic bicyclic guanidine (MTBD), 1,5,7-triazidobicyclo[4.4.0]dec-5-ene (TBD), tetramethylguanidine (TMG), and 4-dimethylaminopyridine (DMAP); using an organic base with stronger alkalinity can reduce the amount of organic base added, and a liquid catalyst with good hydrolysis stability can be obtained at a lower alkali-titanium ratio.

[0050] The titanium compound includes one or more of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate or tetrabutyl titanate.

[0051] The fatty acid includes a chain aliphatic dibasic acid containing 4-20 carbon atoms, and the aromatic dibasic acid includes any one or more of terephthalic acid, isophthalic acid, phthalic acid, 2,5-furandicarboxylic acid, and 2,5-thiophenedicarboxylic acid.

[0052] The amount of catalyst A and catalyst B used alone is 10-100 ppm, preferably 25-50 ppm, based on the mass content of titanium element in the theoretical value of the obtained polyester. Within this preferred composition range, a polyester having both high intrinsic viscosity and good thermal stability can be synthesized.

[0053] More specifically, the preparation method of butanediol ester comprises the following steps: Step 1, subjecting diol, dibasic acid or its diester and catalyst A to esterification reaction at 190-240° C. and normal pressure for 60-240 minutes to obtain an esterification product;

[0054] Step 2, adding catalyst B to the esterification product, reducing the pressure to 5-100 Pa within 30-120 minutes, raising the temperature to 240-260° C., and carrying out polycondensation reaction for 60-300 minutes to obtain the butanediol polyester.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] (1) Catalyst A is in liquid form and is easy to add; the chelated ligand and the organic base in Catalyst A coordinate the titanium atom together, thereby improving the stability of Catalyst A, so that it can still maintain good hydrolysis stability at high temperature (esterification or transesterification reaction temperature), thereby maintaining high catalytic activity, reducing the generation of titanium dioxide or titanium polymer precipitation in the polyester production process, and maintaining a very low THF yield (less than 8%).

[0057] (2) Catalyst B is in liquid form and is easy to add. The phosphate ester in Catalyst B is coordinated with titanium, which solves the problem that some phosphate esters have low boiling points and are easy to volatilize, and the solid phosphate esters are difficult to add, and improves the hydrolysis stability of the catalyst to a certain extent. While maintaining high catalytic activity, Catalyst B significantly improves the color of the polyester product (b* value <10).

[0058] (3) By adopting the preparation method of adding catalyst A in the esterification or transesterification stage and adding catalyst B in the polycondensation stage, a butanediol polyester with an intrinsic viscosity >1.0 dL / g, a light color b* value <10, and a carboxyl content of less than 15 mol / t or even less than 10 mol / t can be obtained.

[0059] (4) The preparation method of the catalyst of the present invention is efficient, economical, and environmentally friendly, and the raw material and preparation costs are low, which will not lead to an increase in the production cost of polyester. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is the appearance of the catalysts prepared in Comparative Example A1, Example A1 and Example B2 after high-temperature hydrolysis. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0062] The raw materials used in the following specific embodiments are all purchased from the market and used directly without treatment. The test and analysis methods used are described as follows:

[0063] Intrinsic viscosity of polyester: The intrinsic viscosity of the polyester sample was measured using a Hangzhou Zhongwang semi-automatic viscometer at a test temperature of 25°C. The solvent used for PBAT and PBST was chloroform, and the solvent used for PBT was phenol / tetrachloroethane (mass ratio w / w = 3 / 2).

[0064] Color of polyester: Hangzhou Color Spectrum desktop CS-821N spectrophotometer, D65 light source, 10° viewing angle, 0° / 45° optical path geometry structure for testing, CIE1976 L*, a*, b* color system. Copolyester is hot-pressed to obtain a disc with a thickness of about 500um as a sample, which is measured close to the light source. Three points are measured in total, and the arithmetic average of the three-point measurement values ​​is taken as the measurement result. After PBT is dried, crushed, and sieved, PBT sample particles are placed in the sample cup to make the sample compact, placed on the measuring hole, and the chromaticity of the sample is measured.

[0065] Esterification rate and THF yield: The refractive index of the effluent was tested at 25°C using an Abbe refractometer. The standard curve of mass concentration (c) and refractive index (n) (c = 11.2007n-14.9247, R 2 =0.9988) to calculate the contents of THF and water in the distillate, and then calculate the esterification rate (the degree of reaction of the carboxyl group) and the THF yield (expressed as the THF / BDO molar ratio).

[0066] High temperature hydrolysis stability test of catalyst: Add the catalyst to be evaluated, water and 1,4-butanediol (BDO) to a 50mL three-necked flask. The composition of the test solution is: the total amount is 25 grams, and the Ti content in the test solution is calculated to be 0.01wt% based on the Ti content in the catalyst, the mass fraction of water is 1wt%, and the rest is BDO. The flask is placed in an oil bath preheated to 210°C and heated, and nitrogen is introduced. A condenser is connected to the top of the flask to condense the refluxed rising steam. The time for the white precipitate to appear in the flask is compared to evaluate the high temperature hydrolysis resistance of the catalyst.

[0067] For convenience, the names of chemicals used in the following specific embodiments are replaced by English abbreviations. In the naming of catalysts, simpler abbreviations are used to represent chemicals used as catalyst components. The correspondence between chemical names and abbreviations is listed in Table 1.

[0068] Table 1 Chemical names and abbreviations

[0069]

[0070] Note: In the naming of catalysts, in order to distinguish the components, the corresponding chemicals are abbreviated with only the first letter capitalized, as shown in brackets

[0071] Examples A1-A7 Synthesis of Catalyst A

[0072] Example A1 Synthesis of Catalyst TEEa

[0073] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 15.6 g (251.3 mmol) of ethylene glycol was added, and 1.75 g (5.14 mmol) of tetrabutyl titanate was slowly added dropwise to the ethylene glycol. After the addition was completed, the flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0074] (ii) 1.27 g (20.83 mmol) of ethanolamine was added to the reaction mixture obtained in step (i), and the reaction was continued at 160° C. with continuous stirring. It was observed that the milky white suspension gradually disappeared until the reaction system became a uniform transparent liquid. The reaction time was about 1 hour, and the product was recorded as catalyst TEEa. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0075] Example A2 Synthesis of Catalyst TETa

[0076] (i) In a 50 mL three-necked flask equipped with a stirring magnet, add 15.6 g (251.3 mmol) of ethylene glycol and 0.775 g (5.19 mmol) of triethanolamine. After the addition is complete, place the flask in a 160°C oil bath and stir for 1 h under nitrogen protection until the mixture is uniform and transparent.

[0077] (ii) 1.75 g (5.14 mmol) of tetrabutyl titanate was slowly added dropwise to the reaction mixture obtained in step (i). After the addition was completed, the mixture was stirred and reacted at 160° C. for 2 h. n-butanol was observed to be distilled out, and the reaction system remained a uniform and transparent liquid, which was recorded as catalyst TETa. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0078] Example A3 Synthesis of catalyst TED

[0079] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 15.6 g (251.3 mmol) of ethylene glycol was added, and 1.75 g (5.14 mmol) of tetrabutyl titanate was slowly added dropwise to the ethylene glycol. After the addition was completed, the flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0080] (ii) 0.77 g (5.05 mmol) of DBU was added to the reaction mixture obtained in step (i), and the mixture was stirred and reacted at 160° C. It was observed that the milky white suspension gradually disappeared until the reaction system became a uniform transparent liquid. The reaction time was about 1 hour, and the product was recorded as catalyst TED. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0081] Example A4 Synthesis of Catalyst TEDbn

[0082] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 15.6 g (251.3 mmol) of ethylene glycol was added, and 1.75 g (5.14 mmol) of tetrabutyl titanate was slowly added dropwise to the ethylene glycol. After the addition was completed, the flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0083] (ii) 0.666 g (5.35 mmol) of DBN was added to the reaction mixture obtained in step (i), and the reaction was continued under stirring at 160° C. It was observed that the milky white suspension gradually disappeared until the reaction system became a uniform transparent liquid. The reaction time was about 1 hour, and the product was recorded as catalyst TEDbn. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0084] Example A5 Synthesis of Catalyst TAaEa

[0085] (i) 2.84 g (10 mmol) of tetraisopropyl titanate was added dropwise to 2.02 g (20 mmol) of acetylacetone at room temperature. After the addition was complete, the solution was subjected to vacuum rotary evaporation at 65°C for 15 min. The pressure during the reaction was 2 kPa. The solution was observed to change from colorless to orange-red, but remained clear and transparent, and isopropanol was distilled out.

[0086] (ii) 1.24 g (20 mmol) of ethanolamine was added to the reaction mixture obtained in step (i), and the mixture was rotary evaporated at 65°C for 15 min. The reaction system was still a uniform transparent liquid. The catalyst was recorded as TAaEa. The hydrolysis stability of the catalyst was evaluated. The results are shown in Table 2.

[0087] Example A6 Synthesis of Catalyst TEaaTa

[0088] (i) 2.84 g (10 mmol) of tetraisopropyl titanate was added dropwise to 2.61 g (20 mmol) of ethyl acetoacetate at room temperature. After the addition was complete, the mixture was subjected to vacuum rotary evaporation at 65°C for 15 min. The pressure during the reaction was 2 kPa. The solution was observed to change from colorless to light yellow, but remained clear and transparent, and isopropanol was distilled out.

[0089] (ii) 2.24 g (15 mmol) of triethanolamine was added to the reaction mixture obtained in step (i), and rotary evaporated at 65°C for 15 min. The reaction system was still a uniform transparent liquid, which was recorded as catalyst TEaaTa. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0090] Example A7 Synthesis of Catalyst TAaTa

[0091] (i) 2.84 g (10 mmol) of tetraisopropyl titanate was added dropwise to 2.02 g (20 mmol) of acetylacetone at room temperature. After the addition was complete, the solution was subjected to vacuum rotary evaporation at 65°C for 15 min. The pressure during the reaction was 2 kPa. The solution was observed to change from colorless to orange-red, but remained clear and transparent, and isopropanol was distilled out.

[0092] (ii) 2.24 g (15 mmol) of triethanolamine was added to the reaction mixture obtained in step (i), and the mixture was rotary evaporated at 65° C. for 15 min. The reaction system was still a uniform transparent liquid, which was recorded as catalyst TAaTa. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0093] Examples B1-B4 Synthesis of Catalyst B

[0094] Example B1 Synthesis of Catalyst TBTpp

[0095] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 13.7 g (152.02 mmol) of 1,4-butanediol was added, and 3.51 g (10.31 mmol) of tetrabutyl titanate was slowly added dropwise to the 1,4-butanediol. After the addition was completed, the flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. The reaction system remained a uniform, clear and transparent solution, and n-butanol was distilled out.

[0096] (ii) 3.26 g (10.00 mmol) of triphenyl phosphate was added to the reaction mixture obtained in step (i), and the reaction was continued under nitrogen protection at 160°C with stirring. It was observed that the solid triphenyl phosphate gradually disappeared, and the reaction system gradually changed into a uniform transparent liquid. The reaction time was about 1 hour, and the product was recorded as catalyst TBTpp. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0097] Example B2 Synthesis of Catalyst TBTpp-2

[0098] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 13.7 g (152.02 mmol) of 1,4-butanediol was added, and 3.51 g (10.31 mmol) of tetrabutyl titanate was slowly added dropwise to the 1,4-butanediol. After the addition was completed, the flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. The reaction system remained a uniform, clear and transparent solution, and n-butanol was distilled out.

[0099] (ii) 4.90 g (15.01 mmol) of triphenyl phosphate was added to the reaction mixture obtained in step (i), and the reaction was continued under stirring at 160° C. under nitrogen protection. It was observed that the solid triphenyl phosphate gradually disappeared, and the reaction system gradually changed into a uniform transparent liquid. The reaction time was about 1 hour, and the product was recorded as catalyst TBTpp-2. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0100] Example B3 Synthesis of Catalyst TBTepa

[0101] (i) 1.71 g (5 mmol) of tetrabutyl titanate was added dropwise to 6.75 g (75 mmol) of 1,4-butanediol at room temperature, and after the addition was complete, the solution was vacuum evaporated at 85°C for 15 min. It was observed that the solution turned light yellow, but remained clear and transparent, and n-butanol was distilled out.

[0102] (ii) 1.68 g (7.5 mmol) of triethyl phosphoacetate was added to the reaction mixture obtained in step (i), and the mixture was rotary evaporated at 85°C for 15 min. It was observed that the reaction system was still a uniform transparent liquid, which was recorded as catalyst TBTepa. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0103] Example B4 Synthesis of Catalyst TBTepa-2

[0104] (i) 1.71 g (5 mmol) of tetrabutyl titanate was added dropwise to 6.75 g (75 mmol) of 1,4-butanediol at room temperature, and after the addition was complete, the solution was vacuum evaporated at 85°C for 15 min. It was observed that the solution turned light yellow, but remained clear and transparent, and n-butanol was distilled out.

[0105] (ii) 2.93 g (13 mmol) of triethyl phosphoacetate was added to the reaction mixture obtained in step (i), and the mixture was evaporated at 85°C for 15 min. It was observed that the reaction system was still a uniform transparent liquid, which was recorded as catalyst TBTepa-2. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2

[0106] Synthesis of Examples C1-C8 Polyesters

[0107] Example C1 Synthesis of copolyester PBST using catalyst A2 and B1 50

[0108] (Note: Catalyst A2 refers to the catalyst prepared in Example A2, referred to as A2. The same is true for the others)

[0109] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TETa prepared in Example A2 was added, and the catalyst dosage was 22 ppm (referring to the mass content of titanium element in the expected polymer, the same below). The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.92 h to obtain an esterification product;

[0110] The catalyst TBTpp prepared in Example B1 was added to the esterification product, the catalyst dosage was 28 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255°C, the pressure was controlled at less than 100 Pa, and the reaction time was 2.9 hours; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.09dL / g, and its L*, a*, and b* values ​​are 78.3, 0.85, and 9.2 respectively.

[0111] Example C2 Synthesis of copolyester PBST using catalyst A3 and B1 50

[0112] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TED prepared in Example A3 was added, and the catalyst dosage was 28 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.03 h to obtain an esterification product;

[0113] The catalyst TBTpp prepared in Example B1 was added to the esterification product, the catalyst dosage was 27 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 2 h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.02dL / g, and its L*, a*, and b* values ​​are 72.6, 1.1, and 8.3 respectively.

[0114] Example C3 Synthesis of copolyester PBST using catalyst A4 and B2 50

[0115] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TEDbn prepared in Example A4 was added, and the catalyst dosage was 25 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.48 h to obtain an esterification product;

[0116] The catalyst TBTpp-2 prepared in Example B2 was added to the esterification product, the catalyst dosage was 25 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 2 h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.06dL / g, and its L*, a*, and b* values ​​are 74.8, 0.58, and 8.7, respectively.

[0117] Example C4 Synthesis of copolyester PBST using catalyst A1 and B2 50

[0118] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TEEa prepared in Example A1 was added, and the catalyst dosage was 25 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.48 h to obtain an esterification product;

[0119] The catalyst TBTpp-2 prepared in Example B2 was added to the esterification product, the catalyst dosage was 25 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 2 h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 0.98dL / g, and the L*, a*, and b* values ​​are 77.0, 0.64, and 7.9 respectively.

[0120] Example C5 Synthesis of copolyester PBST using catalyst A5 and B1 50

[0121] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TAaEa prepared in Example A5 was added in an amount of 45 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.77 h to obtain an esterification product;

[0122] The catalyst TBTpp prepared in Example B1 was added to the esterification product, the catalyst dosage was 29 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 1.15 h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.15dL / g, L*, a*, b* values ​​are 75.9, -0.16, 9.9 respectively.

[0123] Example C6 Synthesis of copolyester PBST using catalyst A5 and B2 50

[0124] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TEaaTa prepared in Example A6 was added in an amount of 25 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.63 h to obtain an esterification product;

[0125] The catalyst TBTpp-2 prepared in Example B2 was added to the esterification product, the catalyst dosage was 25 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 1.75 h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.15dL / g, and the L*, a*, and b* values ​​are 77.6, 0.60, and 9.1 respectively.

[0126] Example C7 Synthesis of copolyester PBST using catalyst A6 and B4 50

[0127] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TAaTa prepared in Example A6 was added, and the catalyst dosage was 39 ppm. The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2.32 h to obtain an esterification product;

[0128] The catalyst TBTepa-2 prepared in Example B4 was added to the esterification product, the catalyst dosage was 26 ppm, and then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 2.22 h; after cooling and pelletizing, PBST was obtained.50 Polyester, its intrinsic viscosity is 0.95dL / g, and the L*, a*, and b* values ​​are 71.7, 0.38, and 9.4 respectively.

[0129] Example C8 Synthesis of Polyester PBT Using Catalysts A3 and B3

[0130] 83 g (0.5 mol) of terephthalic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TED prepared in Example A3 was added, and the catalyst dosage was 25 ppm (referring to the mass content of titanium element in the expected polymer, the same below). The temperature was controlled at 210-225° C., nitrogen was introduced, and an esterification reaction was carried out for 2 hours to obtain an esterification product;

[0131] The catalyst TBTepa prepared in Example B3 was added to the esterification product in an amount of 25 ppm, and then the pressure was gradually reduced to carry out polycondensation under vacuum conditions. The reaction temperature was controlled at 240-255° C., the pressure was controlled at less than 100 Pa, and the reaction time was 1.25 h. After cooling and pelletizing, PBT polyester was obtained, and its intrinsic viscosity was 0.87 dL / g, and the L*, a*, and b* values ​​were 91.5, -0.46, and 4.1, respectively.

[0132] Comparative Example A1

[0133] The hydrolysis stability of commercial tetrabutyl titanate (TBT) catalyst was evaluated. Tetrabutyl titanate was purchased from Beijing Bailingwei Technology Co., Ltd. The results are shown in Table 2.

[0134] Comparative Example A2

[0135] The hydrolysis stability of diisopropyl di(acetylacetonato)titanate (TAa) catalyst was evaluated. Diisopropyl di(acetylacetonato)titanate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The results are shown in Table 2. Comparative Example A3 Synthesis of Catalyst TBTa

[0136] 22.4 g of 1,4-butanediol was added to a 50 mL three-necked flask equipped with a stirring magnet, 1.72 g of tetrabutyl titanate was slowly added dropwise to the above solution, and mixed evenly. Then the flask was placed in a 160°C oil bath and reacted for 2 hours under nitrogen protection. It was observed that n-butanol was distilled out, and the reaction system remained uniform and transparent.

[0137] 0.75 g of triethanolamine was further added to the reaction mixture, mixed evenly, and stirred continuously at 160° C. for 1 hour. The reaction system remained uniform and transparent throughout. The catalyst was recorded as TBTa. The hydrolysis stability of the catalyst was evaluated. The results are shown in Table 2.

[0138] Comparative Example A4 Synthesis of Catalyst TETa-C at Room Temperature

[0139] 15.6 g of ethylene glycol was added to a 50 mL three-necked flask equipped with a stirring magnet, and 1.75 g of tetrabutyl titanate was slowly added dropwise to the ethylene glycol. The mixture was reacted for 2 h at room temperature under nitrogen protection. A light white precipitate was observed to form in the solution.

[0140] 0.775 g (5.19 mmol) of triethanolamine was further added to the reaction mixture, and stirring was continued at room temperature. The precipitate gradually disappeared until the reaction system became a uniform transparent liquid. The obtained catalyst was recorded as TETa-C. The hydrolysis stability of the catalyst was evaluated, and the results are shown in Table 2.

[0141] Comparative Example A5 Synthesis of Catalyst TPTa

[0142] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 19.0 g (249.70 mmol) of 1,3-propylene glycol was added, and 3.41 g (10.02 mmol) of tetrabutyl titanate was slowly added dropwise to ethylene glycol. The flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0143] (ii) 4.50 g (30.16 mmol) of triethanolamine was added to the reaction mixture obtained in step (i), and the mixture was stirred at 160° C. for 1 h. The solution was still a milky white thick suspension. The catalyst was recorded as TPTa.

[0144] Comparative Example A6 Synthesis of Catalyst TmPTa

[0145] (i) In a 50 mL three-necked flask equipped with a stirring magnet, 22.5 g (249.66 mmol) of 2-methyl-1,3-propanediol was added, and 3.41 g (10.02 mmol) of tetrabutyl titanate was slowly added dropwise to the 2-methyl-1,3-propanediol. The flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0146] (ii) 1.50 g (10.05 mmol) of triethanolamine was added to the reaction mixture obtained in step (i), and the mixture was stirred at 160° C. for 1 h. The solution was still a milky white thick suspension. The catalyst was recorded as TmPTa.

[0147] Comparative Example A7 Synthesis of Catalyst TGTa

[0148] (i) In a 50-mL three-necked flask equipped with a stirring magnet, 23.2 g (241.92 mmol) of propylene glycol was added, and 3.41 g (10.02 mmol) of tetrabutyl titanate was slowly added dropwise to the propylene glycol. The flask was placed in an oil bath at 160°C and reacted for 2 h under nitrogen protection. A milky white precipitate was observed in the solution, and the reaction system became a milky white thick suspension, and n-butanol was distilled out.

[0149] (ii) 4.50 g (30.16 mmol) of triethanolamine was added to the reaction mixture obtained in step (i), and the mixture was stirred at 160° C. for 1 h. The solution was still a milky white thick suspension. The catalyst was recorded as TGTa.

[0150] Comparative Example C1 uses catalyst TBT to synthesize copolyester PBST throughout the process 50

[0151] 41.5g (0.25mol) of terephthalic acid, 29.5g (0.25mol) of succinic acid and 90.1g (0.5mol) of 1,4-butanediol were added to a polymerization reactor, and TBT of Comparative Example 1 was added, with a catalyst dosage of 100ppm. The temperature was controlled at 210-225°C, nitrogen was introduced, and an esterification reaction was carried out for 2.13h to obtain an esterification product; then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255°C, the pressure was controlled at less than 100Pa, and the reaction time was 1.5h; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.01dL / g, and its L*, a*, and b* values ​​are 74.2, -0.50, and 13.8 respectively.

[0152] Comparative Example C2 uses catalyst B1 to synthesize copolyester PBST throughout the process 50

[0153] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TBTpp prepared in Example B1 was added, with a catalyst dosage of 100 ppm. The temperature was controlled at 210-225°C, nitrogen was introduced, and an esterification reaction was carried out for 3.02 hours to obtain an esterification product; then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255°C, the pressure was controlled at less than 100 Pa, and the reaction time was 1.5 hours; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 0.97dL / g, and its L*, a*, and b* values ​​are 74.9, 0.86, and 6.0, respectively.

[0154] Comparative Example C3 uses catalyst B3 to synthesize copolyester PBST throughout the process 50

[0155] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TBTepa prepared in Example B3 was added, with a catalyst dosage of 100 ppm. The temperature was controlled at 210-225°C, nitrogen was introduced, and an esterification reaction was carried out for 2.57 hours to obtain an esterification product; then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255°C, the pressure was controlled at less than 100 Pa, and the reaction time was 3.5 hours; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.03dL / g, and its L*, a*, and b* values ​​are 78.2, 1.1, and 8.6 respectively.

[0156] Comparative Example C4 uses catalyst A7 to synthesize copolyester PBST throughout the process 50

[0157] 41.5 g (0.25 mol) of terephthalic acid, 29.5 g (0.25 mol) of succinic acid and 90.1 g (0.5 mol) of 1,4-butanediol were added to a polymerization reactor, and the catalyst TAaTa prepared in Example A7 was added, and the catalyst dosage was 50 ppm. The temperature was controlled at 210-225°C, nitrogen was introduced, and the esterification reaction was carried out for 2.32 hours to obtain an esterification product; then the pressure was gradually reduced, and a polycondensation reaction was carried out under vacuum conditions, the reaction temperature was controlled at 240-255°C, the pressure was controlled at less than 100 Pa, and the reaction time was 1.75 hours; after cooling and pelletizing, PBST was obtained. 50 Polyester, its intrinsic viscosity is 1.03dL / g, L*, a*, b* values ​​are 74.2, -0.28, 15.5 respectively.

[0158] The hydrolysis stability evaluation results of the catalysts synthesized in various examples and comparative examples are summarized in Table 2.

[0159] Table 2 Evaluation results of hydrolysis stability of catalysts prepared in Examples and Comparative Examples

[0160]

[0161] a : refers to the time the catalyst is placed from synthesis to the hydrolysis stability test;

[0162] b : Mass percentage of titanium in the test solution;

[0163] c : The mass percentage of water in the test solution;

[0164] -: Indicates that placement direct testing was not performed or that no testing was performed.

[0165] As can be seen from Table 2, the existing catalysts tetrabutyl titanate and diisopropyl di(acetylacetonato) titanate in Comparative Examples A1 and A2 have very poor hydrolysis stability and both hydrolyze and precipitate in less than 20 minutes at high temperatures.

[0166] From the results of Examples A1-A7, it can be seen that the catalyst A with different compositions synthesized by the method of the present invention has good high-temperature hydrolysis stability and can remain without obvious hydrolysis for two hours under the test conditions (Note: the high-temperature hydrolysis test here is only carried out for 2 hours, so the result does not mean that it can only withstand 2 hours of hydrolysis; in fact, the TETa catalyst prepared in Example A2 remains clear and transparent after 10 hours of high-temperature hydrolysis), and can still maintain the property of hydrolysis stability after being placed for more than 6 months.

[0167] From the results of Comparative Example A3, it can be seen that the hydrolysis stability of the catalyst TBTa with 1,4-butanediol as the ligand is significantly improved compared with TBT, but the hydrolysis stability at high temperature is still not good enough. Under high temperature and water conditions, the TBTa catalyst will also show obvious hydrolysis turbidity within 1.5 hours. It can be seen that the structure of the chelating ligand is the key factor affecting the hydrolysis stability of catalyst A.

[0168] Comparing the TETa catalysts prepared in Example A2 and Comparative Example A4, the difference between the two is that the former is synthesized at a high temperature of 160°C, and the latter is synthesized at room temperature, but surprisingly, the TETa catalyst prepared in Example A2 has excellent high-temperature hydrolysis stability, while the TETa-C prepared in Comparative Example A4 has poor hydrolysis stability at a high temperature of 210°C, which is obviously inferior to the TETa catalyst prepared in Example A2. This shows that appropriate preparation conditions also have an important influence on the hydrolysis stability of the catalyst.

[0169] From the results of Comparative Examples A5, A6, and A7, it can be seen that the catalysts TPTa, TmPTa, and TGTa with 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, and glycerol as ligands, respectively, are still milky white thick suspensions, not liquid catalysts. It can be seen that the structure of the chelating ligand also has an important influence on the morphology of catalyst A.

[0170] From the results of Examples B1-B4, it can be seen that the catalyst B with different compositions synthesized according to the method of the present invention has good hydrolysis stability. The newly synthesized catalyst can be kept for one hour under high temperature test conditions without obvious hydrolysis, and the catalyst with high phosphate content (phosphorus-titanium molar ratio greater than 1.5) can be kept for two hours under high temperature test conditions without obvious hydrolysis, and no hydrolysis precipitation phenomenon occurs. It can be seen that catalyst B also has good hydrolysis stability, but the stability is not as good as catalyst A.

[0171] The appearance of the catalysts prepared in Comparative Example A1 (TBT), Example A1 (TEEa) and Example B2 (TBTpp) after high temperature hydrolysis is as follows: Figure 1 As shown, it can also be seen that the catalyst prepared in the example is still transparent and uniform after high-temperature hydrolysis, and has excellent hydrolysis stability.

[0172] The copolymer compositions, intrinsic viscosities, and THF yields during esterification of the polyesters and copolyesters synthesized in the Examples and Comparative Examples are summarized in Table 3.

[0173] Table 3 Synthesis conditions and results of homopolyester and copolyester prepared in Examples and Comparative Examples

[0174]

[0175] a : refers to the mass fraction of titanium element in the catalyst in the theoretical polyester yield;

[0176] b : Esterification time;

[0177] c : Esterification rate;

[0178] d : The molar ratio of the generated THF to the total amount of BDO added;

[0179] e : polycondensation time;

[0180] f : Intrinsic viscosity, the test temperature is 25.0°C, the solvent used for PBST is chloroform, and the solvent used for PBT is phenol / tetrachloroethane (mass ratio w / w=3 / 2).

[0181] g : The terminal carboxyl content in polyester.

[0182] From the results of Examples C1-C8, it can be seen that the catalytic system used has a very high catalytic activity. 50The synthesis of the present invention can obtain a polyester having an intrinsic viscosity greater than 1.0 dL / g (more than 0.95 dL / g in some embodiments) when the total amount of catalyst Ti is less than 75 ppm and the polycondensation time is less than 3 h. The obtained polyester has good quality, with an L* value greater than 70 and a b* value less than 10, which meets the requirements of relevant national standards.

[0183] When used to synthesize PBT, the esterification rate exceeded 95% when the amount of catalyst A was 25ppm and the esterification time was less than 3.5h; at the same time, the THF yield in the reaction was less than 8%; when the total amount of catalyst was 50ppm and the condensation time was 2h, a polyester with an intrinsic viscosity greater than 0.85dL / g was obtained; and the obtained polyester had excellent quality, with an L* value greater than 90 and a b* value less than 5.

[0184] It can be seen that the catalyst system used in the present invention exhibits high catalytic activity and selectivity for both the esterification stage and the polycondensation stage of butanediol polyester, and the butanediol polyester obtained by the preparation method of the present invention has both high intrinsic viscosity and good color.

[0185] Comparative Example C1 Synthesis of PBST using titanate catalyst TBT 50 , the intrinsic viscosity can be obtained as 1.01dL / g PBST 50 Compared with Comparative Example C1, Examples C1-C7 use less catalyst (in terms of Ti) for PBST 50 When synthesized by using the composite catalyst system of the present invention, the intrinsic viscosity of the obtained polyester is basically the same, all above 1.0 dL / g (some above 0.95 dL / g), which shows that compared with alkoxy titanium, the composite catalyst system of the present invention has a comparable catalytic activity. At the same time, compared with the results of comparative example C1, the color of the polyester synthesized by using the composite catalyst system of the present invention has been significantly improved, and the b* value has been reduced from 13.8 to below 10. This shows that compared with the titanate catalyst, the preparation method of the present invention has fewer discoloration side reactions during the synthesis of PBST.

[0186] Comparative Examples C2 and C3 synthesize PBST by adding catalyst B in the esterification stage and not adding catalyst in the polycondensation stage. 50 When catalyst B was used for esterification, the esterification rate was lower than 95% when the Ti dosage was 50 ppm and the esterification time was greater than 2.5 h. At the same time, the amount of THF generated in the reaction was too much, and the THF yield was higher than 4%, and Example C2 was even higher than 8%. Compared with Comparative Examples C2 and C3, Examples C1-C7 used catalyst A for esterification, and the amount of catalyst A used was less (in terms of Ti), which was used for PBST50 In the esterification reaction, not only the esterification time is shorter, the final esterification rate is higher, and the yield of THF byproducts during the reaction is lower. This shows that compared with catalyst B, catalyst A has higher catalytic activity and better selectivity for esterification, which is obviously due to their excellent hydrolysis stability, especially high temperature hydrolysis stability.

[0187] Comparative Examples C2 and C3 directly carry out polycondensation without adding catalyst in the polycondensation stage. When the catalyst used is TBTpp, a copolyester with an intrinsic viscosity of 0.97 dL / g can be obtained after 1.5 hours of polycondensation, which is less than 1.0 dL / g; when the catalyst used is TBTepa, a copolyester with an intrinsic viscosity of 1.03 dL / g can be obtained after 3.5 hours of polycondensation. This shows that when only catalyst B is used and added in the esterification stage, the polycondensation activity is low, and the polycondensation time must be extended to obtain a copolyester with an intrinsic viscosity greater than 1.0 dL / g. Compared with Comparative Examples C2 and C3, Examples C1-C7 adopt the method of adding catalyst A in the esterification stage and catalyst B in the polycondensation stage, which exerts a better esterification activity of catalyst A. Catalysts A / B work together in the polycondensation stage, and finally obtain a copolyester product with better comprehensive performance.

[0188] Comparative Example C4 synthesizes PBST by adding catalyst A in the esterification stage and adding part of catalyst A in the polycondensation stage. 50 . When the catalyst TAaTa dosage Ti is 25ppm and the esterification time is less than 3h, the esterification rate exceeds 95%; at the same time, the amount of THF generated is small, and the THF yield is 3.56%; when the total catalyst dosage Ti is 50ppm and the polycondensation time is less than 3h, a polyester with an intrinsic viscosity of 1.02dL / g can be obtained; but the obtained polyester is of poor quality, with a b* value greater than 15.5 and a significantly yellowish color. Compared with comparative example C4, the catalyst dosages of examples C1-C7 are equivalent (in terms of Ti), and are used for PBST 50 When synthesized by using the composite catalyst system of the present invention, the intrinsic viscosity of the obtained polyester is basically the same, all above 1.0 dL / g (some above 0.95 dL / g), which shows that compared with the use of catalyst A alone, the composite catalyst system of the present invention has a comparable catalytic activity. Comparing the results of comparative example C4, the color of the polyester synthesized by using the composite catalyst system of the present invention has been significantly improved, and the b* value has been reduced from 15.5 to below 10. This shows that compared with the use of catalyst A alone, the preparation method of the present invention has fewer discoloration side reactions during the synthesis of PBST.

[0189] It can also be seen from the results in Table 3 that the carboxyl content of the polyester synthesized by the preparation method of the present invention is very low, the terminal carboxyl content (CEG) of the obtained PBST copolyester is only 7-17.5 mol / t, and the CEG of the obtained PBT is only 19.2 mol / t. This shows that the polyester synthesized by the preparation method of the present invention has a low terminal carboxyl content. Low carboxyl content is beneficial to improving the processing stability and shelf life of polyester and copolyester.

[0190] In summary, the catalyst system used in the preparation method of the present invention has high catalytic activity and high hydrolysis stability. When used for the synthesis of butanediol polyester, the THF by-product is small, and the obtained butanediol polyester has high intrinsic viscosity, low terminal carboxyl content and good color.

[0191] The present invention is not limited to the above optional implementation modes. Anyone can derive other forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that fall within the scope defined by the claims of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing butanediol polyester, characterized in that: The method comprises the following steps: using diol and dibasic acid or its diester as raw materials, preparing butanediol polyester through esterification and polycondensation; adding catalyst A to catalyze esterification during the esterification process, and adding catalyst B to catalyze polycondensation during the polycondensation process; The diol comprises 80-100 mol % of 1,4-butanediol and 0-20 mol % of other diols; The catalyst A comprises a titanium compound, a chelate ligand and an organic base; the chelate ligand is a diol containing an ortho-hydroxyl group or a β-dicarbonyl compound; the organic base comprises an alcohol amine compound, pyridine, amidine or guanidine; the molar ratio of the chelate ligand to the titanium compound in the catalyst A is (2-100):1; the molar ratio of the organic base to the titanium compound in the catalyst A is (0.5-8):1; When the chelating ligand is a diol containing an ortho-hydroxyl group, the preparation process of the catalyst A comprises: reacting raw materials including a titanium compound, a chelating ligand and an organic base at 160-180° C. for 0.5-4 h to obtain the catalyst A; When the chelating ligand is a β-dicarbonyl compound, the preparation process of the catalyst A comprises: reacting the titanium compound and the chelating ligand at 60-120° C. for 15-30 minutes under vacuum; then adding an organic base and continuing the reaction at normal pressure for 15-30 minutes to obtain the catalyst A; The catalyst B includes a titanium compound, 1,4-butanediol and a phosphate ester; the organic base includes an alcohol amine compound, pyridine, amidine or guanidine; The preparation method of the catalyst B comprises the steps of: The catalyst B is obtained by reacting the raw materials including the titanium compound, 1,4-butanediol and the phosphate ester at 160-180° C. under nitrogen protection for 0.5-4 hours or at 60-120° C. under vacuum conditions for 0.2-1 hour.

2. The method for preparing butanediol polyester according to claim 1, characterized in that: The molar ratio of 1,4-butanediol to the titanium compound in the catalyst B is (8-50):1; And / or, the molar ratio of the phosphate ester to the titanium compound in the catalyst B is (0.1-2):

1.

3. The method for preparing butanediol polyester according to claim 1, characterized in that: The structure of the diol containing ortho-hydroxyl group is shown below: Wherein, R1 and R2 are independently selected from H, CH3, CH2CH3, CH2CH2CH3 or CH2CH2CH2CH3; The β-dicarbonyl compound includes one or more of acetylacetone, ethyl acetoacetate, dimethyl malonate, and diethyl malonate.

4. The method for preparing butanediol polyester according to claim 1, characterized in that: The titanium compound is a compound having the general formula Ti(OR)4, wherein R is a straight chain or branched alkyl group selected from 1 to 10 carbon atoms; And / or, the phosphate ester includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, triisopropyl phosphate, tributyl phosphate, dibutyl phosphate, triphenyl phosphate, and triethyl phosphoacetate; And / or, the other diols include any one or more of ethylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, and cyclohexane-1,4-dimethanol; And / or, the dibasic acid or diester thereof includes any one or more of an aliphatic dibasic acid or diester thereof, an alicyclic dibasic acid or diester thereof, and an aromatic dibasic acid or diester thereof.

5. The method for preparing butanediol polyester according to claim 1, characterized in that: The organic base includes one or more of ethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, triisopropanolamine, diglycolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, DBU, DBN, MTBD, TBD, TMG, and DMAP; And / or, the titanium compound includes one or more of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate; And / or, the fatty acid includes a chain aliphatic dibasic acid containing 4-20 carbon atoms, and the aromatic dibasic acid includes one or more of terephthalic acid, isophthalic acid, phthalic acid, 2,5-furandicarboxylic acid, and 2,5-thiophenedicarboxylic acid.

6. The method for preparing butanediol polyester according to claim 1, characterized in that: The catalyst A and catalyst B are used in amounts of 10-100 ppm, respectively, based on the mass content of titanium element in the theoretical value of the obtained polyester.

7. The method for preparing butanediol polyester according to claim 1, characterized in that: The method comprises the following steps: step 1, subjecting diol, dibasic acid or diester thereof and catalyst A to esterification reaction at 190-240° C. and normal pressure for 60-240 minutes to obtain an esterification product; Step 2, adding catalyst B to the esterification product, reducing the pressure to 5-100 Pa within 30-120 minutes, raising the temperature to 240-260° C., and carrying out polycondensation reaction for 60-300 minutes to obtain the butanediol polyester.

Citation Information

Patent Citations

  • Preparation method of environment-friendly titanium-phosphor coordination composite catalyst, and PBS producing method using environment-friendly titanium-phosphor coordination composite catalyst

    CN105131269A

  • Catalyst system for synthesizing aliphatic-aromatic copolyester and application of catalyst system

    CN113388100A

  • Esterification catalyst and process therewith

    US20050215425A1

  • Esterification catalyst compositions

    WO2001056694A1